Identifying factors perceived to influence the development of elite youth football academy players - Mills, A.; Butt, J.; Maynard, I.; Harwood, C. (Journal of Sports Sciences, 2012)
Based on the developmental theory presented by Gagné (2009), we examined the factors perceived to influence the development of elite youth football players at a critical stage in their progression to the professional level. Transcribed interviews with ten expert development coaches were inductively and deductively content analysed. Conceptualisation of the data revealed six interrelated higher-order categories that represented the factors perceived to either positively or negatively influence player development. These were: awareness (e.g. self-awareness, awareness of others); resilience (e.g. coping with setbacks, optimistic attitude); goal-directed attributes (e.g. passion, professional attitude); intelligence (e.g. sport intelligence, emotional competence); sport-specific attributes (e.g. coachability, competitiveness); and environmental factors (e.g. significant others, culture of game). In this investigation, awareness emerged as a fundamental and mediating element for understanding how young players are able to transition to the professional level. Collectively, the findings underline the multidimensional nature of talent development and suggest that an intricate combination of stage-specific factors must manifest for gifted young players to translate their potential into excellence. Mechanisms by which academies could be helped to shape the characteristics and conditions associated with effective development are discussed.